Stabilisasi Tanah Cl-Ml Menggunakan Semen Dan Difa Soil Stabilizer - Endala Siboro; Muhamad Yusa; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
CL-ML (clay with low plasticity, silt with low plasticity) soil is a type of soil with inconsistent property and low bearing capacity caused by changes in water content. Soil stabilization is required to fix its problematic properties. One of the possible method to fix the soil chemically is soil stabilization with cement and DIFA soil stabilizer as additives. DIFA soil stabilizer is a type of addictive ingredient used in soil stabilization and to solidify and stabilize soil physically and chemically. This study aims to analyze the effective content of cement and DIFA soil stabilizer in increasing the compressive strength of the soil and comparing it with the compressive strength of cement-free soil. Cement content variations used were 3% and 5% from the dry weight of the soil and DIFA soil stabilizer content variations used were 0.6%, 0.8%, and 1% from dry weight of the soil. Shear strength tests were done after 0, 7, and 14 days of submersion. The result of this study shows that the compressive strength of the original soil is 127,78 kPa, which increases to 153,46% after the addition of 5% cement. Then in the 14 days curing time, the compressive strength of soil-5% cement is 1684,09 kPa. The highest compressive strength value is 1711,60 kPa which is obtained when the soil is stabilized with 5% cement addition, 0.6% DIFA soil stabilizer, and 14 days of submersion.Keywords: compressive strength, CL-ML, stabilization, DIFA soil stabilizer, cement